2021
DOI: 10.1107/s1600577521004744
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyl radical mediated damage of proteins in low oxygen solution investigated using X-ray footprinting mass spectrometry

Abstract: In the method of X-ray footprinting mass spectrometry (XFMS), proteins at micromolar concentration in solution are irradiated with a broadband X-ray source, and the resulting hydroxyl radical modifications are characterized using liquid chromatography mass spectrometry to determine sites of solvent accessibility. These data are used to infer structural changes in proteins upon interaction with other proteins, folding, or ligand binding. XFMS is typically performed under aerobic conditions; dissolved molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Further, the oxidative damage when comparing fully aerated to low-oxygen samples demonstrated that the presence of dissolved oxygen significantly affects the amount of oxidative damage incurred by the peptides in solution. Previous XFMS studies of proteins in an anaerobic environment have also shown that oxidative damage is reduced when dissolved oxygen in solution is lowered (24), since the mechanism of oxidative damage in the form of OH moiety addition (and other products) generally relies on the presence of oxygen. One explanation for the reduced damage of peptides in water using high dose rate irradiation is based upon the "oxygen depletion effect" (38)(39)(40), in which oxygen is consumed quickly by reactions under the high dose rate irradiation, and exposure times are short enough that sufficient oxygen for further reactions does not diffuse back into solution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the oxidative damage when comparing fully aerated to low-oxygen samples demonstrated that the presence of dissolved oxygen significantly affects the amount of oxidative damage incurred by the peptides in solution. Previous XFMS studies of proteins in an anaerobic environment have also shown that oxidative damage is reduced when dissolved oxygen in solution is lowered (24), since the mechanism of oxidative damage in the form of OH moiety addition (and other products) generally relies on the presence of oxygen. One explanation for the reduced damage of peptides in water using high dose rate irradiation is based upon the "oxygen depletion effect" (38)(39)(40), in which oxygen is consumed quickly by reactions under the high dose rate irradiation, and exposure times are short enough that sufficient oxygen for further reactions does not diffuse back into solution.…”
Section: Discussionmentioning
confidence: 99%
“…Low-oxygen samples were further prepared by bubbling N 2 gas through samples for one min and then cycling into a nitrogen environment in a Coy Anaerobic Chamber. Oxygen levels were then measured in the anaerobic chamber prior to triple-bagging samples in plastic bags with zip closures for transport to either the synchrotron X-ray beamline or the XRAD X-ray instrument, as previously described ( 24 ). Before transport, O 2 levels in the low-oxygen samples measured 1–3%.…”
Section: Methodsmentioning
confidence: 99%
“…OH in particular generates covalent modifications to sidechains, with the most common modifications including an -OH or carbonyl addition, with some dependency on dissolved oxygen content in solution. [24][25]…”
Section: The Structural Footprinting Assaymentioning
confidence: 99%
“…With this method, the synchrotron X‐ray energy deposited in aqueous buffer is absorbed by water molecules, generating ⋅OH, electrons and secondary radical species [24] . The ⋅OH molecule and electrons are the most reactive of these to protein sidechains, and ⋅OH in particular generates covalent modifications to sidechains, with the most common modifications including an ‐OH or carbonyl addition, with some dependency on dissolved oxygen content in solution [24–25] …”
Section: The Structural Footprinting Assaymentioning
confidence: 99%
“…HRPF is an umbrella term for covalent labeling approaches employing •OH adducts, where the •OH can be generated by a variety of approaches: radiolysis of water by X-rays, γ-rays, electron beams, electric discharges or plasma sources; decomposition of hydrogen peroxide (H 2 O 2 ) using transition metal-based Fenton chemistry; and photolysis of H 2 O 2 using lasers (FPOP) or a high-pressure flash oxidation lamp. Among these •OH sources, high-intensity X-ray synchrotron beamlines played an essential role in the beginning of the HRPF field and continue to be important resources for HRPF method development and applications. X-ray beamlines deliver a measurable, reproducible, and controlled •OH dose on microsecond to millisecond (and longer) time scales. The availability of a high •OH dose at synchrotron beamlines for the structural biology community has allowed studies of complex and highly scavenging systems such as virus assembly, neurodegenerative diseases, epitope mapping, and time-resolved macromolecular dynamics. Until now, MS analysis steps for X-ray irradiated samples have been carried out at geographically distant sites from the synchrotron, resulting in a slow feedback loop between sample chemistry optimization, beamline experiments, and data analysis .…”
Section: Introductionmentioning
confidence: 99%